Improving public service culture with reduction of interest conflicts in State-Owned Enterprises (SOEs) task enforcement in emerging markets - case in Vietnam - Hue Ly Thy (Zielona Góra: Faculty of Economics and Management Press)
Nowadays, many developing countries such as China, India and Vietnam, etc. have been trying to improve public service culture in public service organizations through eliminating corruption, more integrity, and training and improving good corporate governance.
Keywords: public service culture; public tasks; conflict of interests; administration; kultura służby publicznej; zadania publiczne; konflikt interesów; administracja